Removal of reactive red 4 dye using chitosan- epichlorohydrin/ TiO2 nanocomposite: application of response surface methodology / Nurul Najwa Abd Malek … [et al.] - Abd Malek, Nurul Najwa; Mohammed, Ibrahim Awad; Reghioua, Abdallah; Yousif, Emad; Jawad, Ali H. (Faculty of Applied Sciences, 2020)
Chitosan-epichlorohydrin/TiO2 composite was synthesized to be employed as an adsorbent for the removal of reactive red 4 (RR4) dye from aqueous solution. Response surface methodology (RSM) with 3-level Box-Behnken design (BBD) was utilized for the optimization of the removal of RR4. The process key variables which include adsorbent dose (A: 0.5 – 1.5 g), pH (B: 4 – 10) and time (30 – 80 min) were selected for the optimization process. The experimental data for RR4 removal were statistically analysed using analysis of variance (ANOVA). The significant interaction between key parameters on RR4 removal efficiency was observed by interaction between AB and AC. The highest RR4 removal (95.08%) was obtained under the following conditions; adsorbent dose (1.0 g), pH 4 and time of 80 min.